Privacy Preserving Attribute based encryption in Personal Healthcare Records - G.K.Sandhia, Parichay Jash, Yawar Manzoor (International Journal of Advanced Science and Technology, 2020)
Personal health records (PHR) have emerged as a patient model of health information exchange. The PHR service allows the patient i.e the users to create, manage, alter privileges and manage their health information in one place through the web, making storage, retrieval, and sharing of medical information more effective. In particular, each patient is promised full management of his or her medical records and may share his or her health information with dozens of users, including health care providers, family members or friends. The main purpose of this research project is to propose a novel framework for the sharing of personal health records on a cloud computer. Keeping in mind the reliability of cloud servers, we note that to fully realize the patient’s concept, patients must have complete control of their privacy by encrypting their PHR files to allow for better access and enhanced security. We propose a two-party key output policy that can ensure that no central authority or cloud service provider can compromise the privacy of each user’s identity. In addition, we introduce the concept of an attribute in terms of weight, which is given to maximize the specification of an attribute, which can extend the annotation from an engineering to an argumentative context, but also highlight the complexity of an access policy. Therefore, both the cost of maintaining and coding the cipher text is released. Performance analysis and security evidence indicate that the proposed system is capable of achieving valid and secure sharing of computer sharing in the cloud. Keywords: PHR.